Vision-Based Parking Entry Control System - Wahap, Ahmad Ridhwan; Saharudin, Shahrulnafiin (ELEKTRIKA- Journal of Electrical Engineering, 2018)
Vision-based control systems are very promising in the Intelligent Transportation System (ITS). This paper proposes a system that use the vision system to control vehicle entry at the bridge gate at a certain facility. The system detects the presence of the car and captures the front car image to proceed to plate recognition process. Vehicle plate region is extracted using the size filtering, image thresholding and object counting algorithms. Optical character recognition technique is used in the recognition module. The result from the recognition module is then compared to the record in the database for information like the vehicle owner name, type of car, etc. The overall system is implemented and simulated in LabVIEW and the performance of recognition is tested on the real image. The system can successfully detect and recognize the plate number with minimum error.